2022
DOI: 10.1001/jamanetworkopen.2022.47330
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic Experiences and Symptoms of Pandemic-Associated Traumatic Stress Among Mothers in the US

Abstract: ImportanceThe primary outcomes of the COVID-19 pandemic on the mental health of women with children remain largely unknown.ObjectivesTo identify and describe clusters of mothers of children participating in the Environmental influences on Child Health Outcomes (ECHO) Program that characterize pandemic-associated hardships, coping mechanisms, and behaviors, and to evaluate associations between pandemic-associated hardships, coping strategies, and behavior changes with pandemic-associated traumatic stress sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Risk and protective factors identified here can be ascertained prenatally, at birth, and prior to postnatal discharge to the home community to individualize family supports. 71 , 72 When initiated earlier, behavioral and emotional interventions are more effective, 73 , 74 , 75 , 76 , 77 with potential to prevent escalation among children with borderline symptoms. Toward the goal of disrupting persisting dysregulation and facilitating resilience, the cumulative risks and behavioral indicators identified inform best practices and future research.…”
Section: Discussionmentioning
confidence: 99%
“…Risk and protective factors identified here can be ascertained prenatally, at birth, and prior to postnatal discharge to the home community to individualize family supports. 71 , 72 When initiated earlier, behavioral and emotional interventions are more effective, 73 , 74 , 75 , 76 , 77 with potential to prevent escalation among children with borderline symptoms. Toward the goal of disrupting persisting dysregulation and facilitating resilience, the cumulative risks and behavioral indicators identified inform best practices and future research.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that MPD has increased since the beginning of the COVID-19 pandemic (Adams et al, 2021;Eales et al, 2021;Kerr et al, 2022;Marchetti et al, 2020;Spinelli et al, 2020). However, recent findings show that some mothers are less affected by the negative consequences of the pandemic, and they have a more developed sense of parenting (Bastain et al, 2022;Xiao, 2024). Given that not all mothers are equally affected by the challenges posed by the pandemic, it is important to further investigate factors that might lead to individual differences in MPD during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the change in the level of psychological distress varies across individuals. A large‐scale cohort study conducted with almost 12,000 mothers from the United States revealed maternal profiles of high and low change in psychological distress levels during the pandemic (Bastain et al, 2022). Although some mothers adapted easily to the new living conditions and enjoyed spending more time with their children, other mothers experienced elevated levels of psychological distress (Calarco et al, 2020).…”
Section: Covid‐19 Impact On Familiesmentioning
confidence: 99%
“…The diversity of the effects of the COVID-19 pandemic across different social categories has been covered more in North American research. In their study, Bastain et al (2022) found that, while more changes in everyday life caused by the pandemic and higher PTS were reported by socioeconomically advantaged respondents, the association between PTS and higher pandemic-associated hardships, coping mechanisms, and behavioral changes was greater in the less socioeconomically advantaged cluster. In a Canadian study, Hirani and Wagner (2022) showed that refugee mothers were at a high risk of experiencing add-on stressors due to isolation, difficulty in accessing health care, COVID-19-related restrictions in hospitals, limited follow-up care, limited social support, financial difficulties, and compromised nutrition.…”
Section: Mothers' Well-being During Covid-19mentioning
confidence: 92%